Approche Méthodologique D’évaluation De Susceptibilité Des Versants Aux Glissements De Terrain Par Un Modèle Volumique De L’aléa ; Application Au Secteur De Boujibar Al Hoceima (Rif, Maroc) - Allal Labriki; Saïd Chakiri; Wafae Nouaim; Mohamed Allouza; Jamil Ezzayani (European Scientific Journal, ESJ, 2016)
This paper presents a new assessment technique of slopes landslide susceptibility, through a geometrical solid model of hazard in reliance on application and comparison of two different approaches (probability and determinist). Here we present a complete methodology for resolving all the technical difficulties encountered during the application of deterministic approach on a catchment basin scale, and to generate an estimating model of hazard not only on the ground surface but also in depth. Indeed, the application of this approach in the area of Boujibar in the south of Al Hoceima city has allowed to specify that, the deterministic method based on factor of safety (Fs) calculation for hazard evaluation of catchment basin is the most adapted and most suitable method on a local and regional scale.